Combining modern tracking data and historical records improves understanding of the summer habitats of the Eastern Lesser White‐fronted Goose Anser erythropus. Issue 9 (9th March 2021) - Tian, Haitao; Solovyeva, Diana; Danilov, Gleb; Vartanyan, Sergey; Wen, Li; Lei, Jialin; Lu, Cai; Bridgewater, Peter; Lei, Guangchun; Zeng, Qing
Abstract: The Lesser White‐fronted Goose ( Anser erythropus), smallest of the "gray" geese, is listed as Vulnerable on the IUCN Red List and protected in all range states. There are three populations, with the least studied being the Eastern population, shared between Russia and China. The extreme remoteness of breeding enclaves makes them largely inaccessible to researchers. As a substitute for visitation, remotely tracking birds from wintering grounds allows exploration of their summer range. Over a period of three years, and using highly accurate GPS tracking devices, eleven individuals of A. erythropus were tracked from the key wintering site of China, to summering, and staging sites in northeastern Russia. Data obtained from that tracking, bolstered by ground survey and literature records, were used to model the summer distribution of A. erythropus . Although earlier literature describes a patchy summer range, the model suggests a contiguous summer habitat range is possible, although observations to date cannot confirm A. erythropus is present throughout the modeled range. The most suitable habitats are located along the coasts of the Laptev Sea, primarily the Lena Delta, in the Yana‐Kolyma Lowland, and smaller lowlands of Chukotka with narrow riparian extensions upstream along major rivers such as the Lena, Indigirka, and Kolyma. The probability of A. erythropus presence is related to areas with altitude less than 500 m with abundant wetlands, especially riparian habitat, and a climate with precipitation of the warmest quarter around 55 mm and mean temperature around 14°C during June‐August. Human disturbance also affects site suitability, with a gradual decrease in species presence starting around 160 km from human settlements. Remote tracking of animal species can bridge the knowledge gap required for robust estimation of species distribution patterns in remote areas. Better knowledge of species' distribution is important in understanding the large‐scale ecological consequences of rapid global change and establishing conservation management strategies. Abstract : The extreme remoteness of breeding enclaves makes the population largely inaccessible to researchers. In the study, we modeled summering range of the East Asian Lesser White‐front Goose Anser erythropus sub‐population by combining GPS tracking data, historical ground survey records, and literature sources, and confirmed a contiguous summer range, rather than patchy habitats suggested by earlier literatures.